Transformation of Physics Learning: The Use of Powtoon Animation and VAK Model to Enhance Learning Motivation Viewed from Students' Inductive Reasoning Ability - Farizi, Zakaria Al; Sahlan, Sahlan; Rusdin, Muhamad Epi; Fitriani, Nadya; Abdullah, Abdullah (Universitas PGRI Semarang, 2024)
Development of Powtoon Animation Media with the VAK Model to Increase Students' Physics Learning Motivation in terms of Inductive Reasoning Ability. This study aims to examine the results of the development of Powtoon animation media with the VAK model on the variables of students' physics learning motivation in terms of inductive reasoning. To obtain the results of student learning motivation, it was carried out using the Posttest only control group research design. The design of this study uses two test classes, namely experimental and control. Data collection was carried out at the end of the lesson. From the results of both it was found that the motivation of the experimental class students was higher than that of the control class. In addition, to measure the effect of covariates on the test variables, covariate analysis (anacova) was carried out. The result is that students' inductive reasoning contributes 22% of their effective contribution. This shows that there is an addition of every 1% of the predictor variable to the increase in the dependent variable in the form of student learning motivation of 0.516.